Image representation study on the impact of resettlement Che Wong tribe at Kuala Gandah, Lanchang Pahang / Fadli Abdul Razak - Abdul Razak, Fadli (2014)
The Che Wong is one of the nineteen original Orang Asli people groups living in Peninsular Malaysia. They are belongs to the Senoi subgroup. The Che Wong is founded in a group that are living near the villages of other races and in the jungles. This research will focus on Che Wong tribe at Kuala Gandah Lanchang, Pahang. After the resettlement made by the policies maker, the immortality of this ethnic culture become one of the main issue. With the availability of reference materials such as video and print media it will help to provide continuity stories of their ancestors (storyteller) that cannot be eliminated by modernization. Expectations with the preparation of this paper, will be a reference to the young generation of Che Wong tribes to preserve their culture and their original genealogies. At the same time, the policy maker should listen to their opinions well before making a decision that could lead to culture shock of Che Wong communities whose originally living in the calm forest. With this document, they can be understand and symphatize with the fate encountered by indigenious people. By constructing a systematic research documentation, it can bridge the gap between the needs Che Wong tribe with policy maker, as well as the future of the aboriginal tribe in Malaysia.